Pharmacology, pharmacokinetics, and metabolism of the DNA-decoy AYX1 for the prevention of acute and chronic post-surgical pain. Issue 1 (April 2017) - Mamet, Julien; Harris, Scott; Klukinov, Michael; Yeomans, David C; Donahue, Renee R; Taylor, Brad K; Eddinger, Kelly; Yaksh, Tony; Manning, Donald C
Background: AYX1 is an unmodified DNA-decoy designed to reduce acute post-surgical pain and its chronification with a single intrathecal dose at the time of surgery. AYX1 inhibits the transcription factor early growth response protein 1, which is transiently induced at the time of injury and triggers gene regulation in the dorsal root ganglia and spinal cord that leads to long-term sensitization and pain. This work characterizes the AYX1 dose-response profile in rats and the link to AYX1 pharmacokinetics and metabolism in the cerebrospinal fluid, dorsal root ganglia, and spinal cord. Results: The effects of ascending dose-levels of AYX1 on mechanical hypersensitivity were measured in the spared nerve injury model of chronic pain and in a plantar incision model of acute post-surgical pain. AYX1 dose-response profile shows that efficacy rapidly increases from a minimum effective dose of ∼ 0.5 mg to a peak maximum effective dose of ∼ 1 mg. With further dose escalation, the efficacy paradoxically appears to decrease by ∼ 30% and then returns to full efficacy at the maximum feasible dose of ∼ 4 mg. The reduction of efficacy is associated to doses triggering a near-saturation of AYX1 metabolism by nucleases in the cerebrospinal fluid and a paradoxical reduction of AYX1 exposure during the period of early growth response protein 1 induction. This effect is overcome at higher doses that compensate for the effect of metabolism. Discussion: AYX1 is a competitive antagonist of early growth response protein 1, which is consistent with the overall increased efficacy observed as dose-levels initially escalate. Chemically, AYX1 is unprotected against degradation by nucleases. The sensitivity to nucleases is reflected in a paradoxical reduction of efficacy in the dose-response curve. Conclusions: These findings point to the importance of the nuclease environment of the cerebrospinal fluid to the research and development of AYX1 and other intrathecal nucleotide-based therapeutics.